2016
DOI: 10.1007/s10552-016-0720-y
|View full text |Cite
|
Sign up to set email alerts
|

Residential mobility and the risk of childhood leukemia

Abstract: Our results do not indicate that higher residential mobility or moving to municipalities with more inhabitants is associated with risk of childhood leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…From 1975 to 2015, the population growth happened almost in parallel in both communities and was almost of the same size in absolute numbers (percentage given in brackets): 5285 (21%) and 5496 (80%), in Geesthacht and Elbmarsch, respectively. A recent cohort study from Switzerland showed that population mixing may have an influence on the risk of childhood leukaemia A c c e p t e d M a n u s c r i p t 17 (Lupatsch et al, 2016), while a case-control study from Finland didn't find any evidence that childhood leukaemia risk is related to population mobility (Jarvela et al, 2016), although there was a suggestive result of a reduced risk with residential mobility at ages 1-2 years. In his reply to Jarvela et al (2016) Kinlen pointed out that the population mixing conditions in Finland do not allow to test Kinlen's hypothesis, because there is no marked influx into a remote rural area (Kinlen 2016), which also applies to the Krümmel cluster.…”
Section: Discussionmentioning
confidence: 99%
“…From 1975 to 2015, the population growth happened almost in parallel in both communities and was almost of the same size in absolute numbers (percentage given in brackets): 5285 (21%) and 5496 (80%), in Geesthacht and Elbmarsch, respectively. A recent cohort study from Switzerland showed that population mixing may have an influence on the risk of childhood leukaemia A c c e p t e d M a n u s c r i p t 17 (Lupatsch et al, 2016), while a case-control study from Finland didn't find any evidence that childhood leukaemia risk is related to population mobility (Jarvela et al, 2016), although there was a suggestive result of a reduced risk with residential mobility at ages 1-2 years. In his reply to Jarvela et al (2016) Kinlen pointed out that the population mixing conditions in Finland do not allow to test Kinlen's hypothesis, because there is no marked influx into a remote rural area (Kinlen 2016), which also applies to the Krümmel cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Unless these population mixing conditions exist, it is unlikely that an effect will be found. As the authors acknowledge ''in Finland overall, there has not been any major population influx or increased residential mobility during the study period'' [1], so their study hardly warrants a conclusion about the validity of the rural population mixing hypothesis. In contrast, supporting evidence from studies of unusual population mixing in rural areas under various circumstances is now extensive [3].…”
mentioning
confidence: 84%
“…The authors [1] stated that the latter hypothesis was supported by the large UK study by Law et al [4], but overlooked the subsequently revised analysis by Roman et al [5] which found results directly contrary to those predicted by the Greaves hypothesis.…”
mentioning
confidence: 96%
See 2 more Smart Citations